Heterogeneity and evolutionary change: Empirical conception, findings and unresolved issues - Uwe Cantner; Horst Hanusch (Universität Augsburg, Institut für Volkswirtschaftslehre, 1999)
In this position paper we deal with the conception of heterogeneity as both the force and the result of evolutionary change. We ask, how this heterogeneity can be measured empirically and how we can get a measure which allows to get a broad comparable empirical account especially on several levels of aggregation. Based on this discussion we suggest that for several questions the measures of total factor productivity (TFP) and local changes of TFP seem to be acceptable candidates for measuring heterogeneity and its dynamics. Examples out of a number of empirical investigations applying this measures show how interesting empirical facts about evolutionary change on several levels of aggregation can be detected. The paper concludes by raising a number of unresolved issues mainly related to the question about the relationship between evolutionary dynamics on several levels of aggregation.
urn:nbn:de:bvb:384-opus4-276740
Keywords: O3; O14; O47; C6; C43; 330